(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article examines the features of the geological structure of the Jurassic deposits of Eastern Ustyurt. Terrigenous deposits of Lower Jurassic age are noted to be of low thickness throughout Eastern Ustyurt. The sediments are composed predominantly of sandstones and siltstones, with a high content of carbonized residues. The Lower Jurassic sequence is composed of interbedded terrigenous rocks (sandstones, mudstones, siltstones, gravelites), while a clearer differentiation of sediments and the presence of pure differences are observed in comparison with the overlying Upper and Middle Jurassic deposits, which is reflected by the presence in the section of thick up to 1149 (Karaaudan) m and more layers of sandstones and clays.